The Effect of Application Interval and Concentration of Liquid Organic Fertilizer on the Growth and Yield of Eggplant: Pengaruh Interval Waktu dan Konsentrasi POC terhadap Pertumbuhan dan Hasil Tanaman Terung Ungu - Selvia Mauradilla Utami; Djarwatiningsih P Soedjarwo; Widi Wurjani (Journal of Applied Plant Technology, 2026)
Eggplant (Solanum melongena L.) is a horticultural crop with significant potential for development. The application of liquid organic fertilizer (POC) sprayed on leaves at appropriate intervals and concentrations can be a solution for providing essential nutrients to plants, thereby achieving optimal crop yields. This study aims to evaluate the best combination of application interval and POC concentration in cultivating purple eggplant. The study was designed using a Split-Plot Design. The sub-plots (application intervals) were divided into W1 = every 5 days, W2 = every 10 days, and W3 = every 15 days. The main plots (POC concentrations) were divided into K1 = 4 ml/l, K2 = 6 ml/l, and K3 = 8 ml/l. The results showed that the combination of application intervals and POC concentrations significantly affected the flowering age of the plants. The best combination was found with a 5-day application interval and a POC concentration of 8 ml/l.